DEVELOPMENT OF FINANCIAL TECHNOLOGIES UNDER THE INFLUENCE OF THE COVIN-19 CORONOVIRUS PANDEMIC - GAVATIUK, L. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the current development of financial technologies, and also emphasizes that since the reform and opening of the market economy, Ukraine is in a state of continuous deepening of reforms, and it is increasingly contributing to the development of social progress. Among them, information technology is gradually becoming one of the driving forces of social development and have a great impact every day. Guided by the impression of information technology, the manufacturing and financial industries have also developed various systems of services and products, achieving the goal of gradual development and construction of a modern financial industry. The trends of changes caused by COVID-19, which have a profound impact on the model of financial services, the future economic and financial systems, are studied. The main stages of modernization of the financial sector are identified, and the next three stages of changes in the modernization of this industry are considered: the first - paying more attention to data optimization and standardization, using the method of large numbers; second - further introduction of new technologies for the promotion of the Internet, mobile and intelligent products and services, the financial industry will continue to cover artificial intelligence, blockchain, etc .; third - the development of institutional rules more understandable, transparent and standardized. It is emphasized that it was the continuous development of science and technology that contributed to the effective process of modernization of the financial sector, and at the same time it was he who began the rise of financial system reform on a global scale. It is mentioned that currently Ukraine is facing a trend of digital transformation. Now is the window period for the development of financial technologies. It is necessary to avoid repeating the mistakes of Internet finance and use the main historical opportunities for development. Currently, talent, technology, data, capital, industry, supervision, policy, equipment and culture are the nine main elements of financial technology development. The impact of financial digitization on the macro and macro level of financial institutions is summarized, and current negative factors and ways to solve them are identified on the issue of privacy protection and rational use of data, which are practical difficulties facing the inability to maximize the value of data elements.